Effectiveness of the inspection of the industry and commerce tax in the municipality of Mosquera (2018)
Taxes are the main source of resources available to the State to finance their investment projects and expenses and thereby achieve the goals that frame his reason for being as a Social State of Law. However, the responsibility of paying taxes is not a situation that is welcomed with the best attitude and enthusiasm on the part of citizens, which has a logical explanation due to the cases of corruption and mismanagement that are given to resources obtained via taxes and that very often are the main issue in the different media, which generates in the taxpayers feelings of dissatisfaction and the desire to evade their fiscal responsibility. For this reason, the municipalities have a strong responsibility regarding the handling of their tax revenues, which should not be left solely in the payment voluntarily made by taxpayers, which, as mentioned before, has been depleted in recent years. on the contrary, it must incorporate into its tax management aspects of creativity, monitoring, technology, resources and other elements with a view to achieving sufficient funds to finance the plans and projects contained in the municipal government programs. Aware of this situation, the municipality of Mosquera Cundinamarca, has been implemented over the past 10 years, one of the most important and effective actions in tax management: the audit, which has allowed him to achieve the increase in the collection of its principal source of own resource and with it, the execution of infrastructure works of great impact and the development of important projects of social investment that have been fundamental aspects to achieve an important recognition at regional level.